2021
DOI: 10.1038/s41598-021-85586-8
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug-drug interactions of antiretrovirals and antimicrobials detected by three databases

Abstract: Standard treatment for HIV infection involves a combination of antiretrovirals. Additionally, opportunistic infections in HIV infected patients require further antimicrobial medications that might cause drug-drug interactions (DDIs). The objective of this study was to to compare the recognition of DDIs between antiretrovirals and antimicrobials by three proprietary databases and evaluate their concordance. 114 items of antiretrovirals and antimicrobials from the National List of Essential Medicines of Thailand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The two electronic databases reported 488/3,000 (16%) pairs of potential DDIs. This value is between our two previous potential DDI reports of antiretrovirals/antimicrobials (3%-4%) and metabolic syndrome medications (18%-20%) [12,13]. Considering the severity of potential DDIs reported by Micromedex, 191/271 pairs (70%) were reported as contraindicated or major in severity, compared with 70% for antiretrovirals/antimicrobials and 20% for metabolic syndrome medications.…”
Section: Plos Onementioning
confidence: 44%
“…The two electronic databases reported 488/3,000 (16%) pairs of potential DDIs. This value is between our two previous potential DDI reports of antiretrovirals/antimicrobials (3%-4%) and metabolic syndrome medications (18%-20%) [12,13]. Considering the severity of potential DDIs reported by Micromedex, 191/271 pairs (70%) were reported as contraindicated or major in severity, compared with 70% for antiretrovirals/antimicrobials and 20% for metabolic syndrome medications.…”
Section: Plos Onementioning
confidence: 44%
“…One of such is DDI of lopinavir/ritonavir versus buprenorphine where both lopinavir and ritonavir may increase the concentration of buprenorphine, and thus monitoring and adjusting dose are recommended by the NICE 35 , 36 ; another example is DDI of darunavir/cobicistat/emtricitabine/tenofovir alafenamide (DRV/c/FTC/TAF) versus clotrimazole where antifungals like clotrimazole inhibiting CYP3A may decrease the clearance of darunavir and cobicistat, and thus clinical monitoring is recommended by the European Medicines Agency 37 . Interestingly, Vivithanaporn et al 38 reported a significant inconsistency in severity grading across three major DDI databases – Drugs.com, Micromedex and the Liverpool HIV Interaction. A number of drug pairs between ARVs and antimicrobials were shown to have poor concordance in the DDI recognition, e.g., minor or none by Micromedex and Drugs.com but major (Amber/Red) by the Liverpool HIV Interaction database (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…ART adherence in Iran in previous studies ranged from 54.4-85.0% (10,11). Fourth, since the self-medication of drugs in Iran is high (67%) (12,13), drug-drug interaction with other medicines including antibiotics, herbal medicine, or even sedatives can be another reason for the high prevalence of HIV drug resistance (14,15).…”
Section: Discussionmentioning
confidence: 99%